CORTICAL MICROTUBULE DISORDERING1 Is Required for Secondary Cell Wall Patterning in Xylem Vessels. Issue 12 (13th November 2017) - Sasaki, Takema; Fukuda, Hiroo; Oda, Yoshihisa
Abstract : A novel microtubule-associated protein is required for the pitted secondary cell wall patterning in xylem vessels. Abstract: Proper patterning of the cell wall is essential for plant cell development. Cortical microtubule arrays direct the deposition patterns of cell walls at the plasma membrane. However, the precise mechanism underlying cortical microtubule organization is not well understood. Here, we show that a microtubule-associated protein, CORD1 (CORTICAL MICROTUBULE DISORDERING1), is required for the pitted secondary cell wall pattern of metaxylem vessels in Arabidopsis thaliana . Loss of CORD1 and its paralog, CORD2, led to the formation of irregular secondary cell walls with small pits in metaxylem vessels, while overexpressing CORD1 led to the formation of abnormally enlarged secondary cell wall pits. Ectopic expression of CORD1 disturbed the parallel cortical microtubule array by promoting the detachment of microtubules from the plasma membrane. A reconstructive approach revealed that CORD1-induced disorganization of cortical microtubules impairs the boundaries of plasma membrane domains of active ROP11 GTPase, which govern pit formation. Our data suggest that CORD1 promotes cortical microtubule disorganization to regulate secondary cell wall pit formation. The Arabidopsis genome has six CORD1 paralogs that are expressed in various tissues during plant development, suggesting they are important for regulating cortical microtubules during plant development.